Unraveling the mechanisms of propofol-induced psychological dependence: a multi-omics approach linked to gut microbiota in hippocampal function - Wang, Li; Wang, Tangyi; Lei, Yadian; Su, Yudong; Lin, Yuxin; Wu, Zhijing; Wu, Qiong; Zhang, Shoude; Wang, Haiyan (Frontiers in Medicine, 2025)
IntroductionDrug abuse is becoming a global public health crisis. According to the United Nations, the number of drug users worldwide has increased dramatically over the past decade, with a surge in the number of drug abusers. The problem was exacerbated by the expanding market for illicit drugs and the increasing availability of synthetic drugs such as fentanyl. Clinical drug abuse is a problem that requires particular attention, and the potential addictive properties of some drugs and their mechanisms of action are currently unknown, which limits the development and implementation of drug addiction intervention strategies.MethodsEight-week-old C57BL/6J mice were used as study subjects. A mental dependence model was established using the conditional position preference experiment (CPP), and the hippocampal tissues of the model mice were subjected to RNA-seq transcriptome sequencing, LC–MS non-targeted metabolome sequencing, and intestinal macro-genome sequencing in order to discover propofol mental dependence signature genes. Correlation analyses of transcriptomics and metabolomics were performed using the Spearman method, and gene-metabolite networks were mapped using Cytoscape software. Real-time fluorescence quantitative PCR and immunoprotein blotting (Western blotting) methods were used to validate the characterized genes.ResultsAfter the conditioned position preference experiment, the conditioned preference scores of the 75 mg/kg propofol and 2 g/kg alcohol groups were significantly higher than those of the control saline group. 152 differential genes and 214 differential metabolites were identified in the 75 mg/kg group. Cluster analysis revealed that changes in the neuroactive ligand receptor pathway were most pronounced. Gut microbiomics assays revealed significant changes in five differential enterobacterial phyla (Campylobacter phylum, Thick-walled phylum, Anaplasma phylum, Actinobacteria phylum, and Chlorella verticillata phylum) in the 75 mg/kg propofol group, which may be related to changes in the differential expression of dopamine.DiscussionThese findings suggest that 75 mg/kg propofol has a significant mind-dependent effect on the biology of drug addiction through neuroactive ligand-receptor interaction pathways in conjunction with the tricarboxylic acid cycle, and the metabolic pathways of alanine, aspartate, and glutamate that may influence intestinal microbial changes through bidirectional signaling.